The Effect of Profitability, Liquidity and Company Size on Capital Structure in Companies Listed on the Indonesian Stock Exchange - Ica Wulandari; Ika Wulandari (Jurnal Syntax Admiration, 2024)
This study investigates the effect of profitability, liquidity, and firm size on the capital structure of firms listed on the Indonesia Stock Exchange (IDX). Using data from manufacturing firms, the study found that profitability and liquidity have a negative and significant influence on capital structure decisions, with more profitable firms tending to rely on less debt and more internal sources of funds. However, firm size does not consistently have a significant negative impact on capital structure, suggesting that external factors such as capital market conditions and economic policies have a more dominant role in determining a firm's capital structure. These results provide important insights for financial practitioners in designing appropriate funding strategies to maximise firm value and effectively manage financial risk in the Indonesian capital market.